Analysis of the Impact of RMB Exchange Rate Changes on the Upgrading of Chinese Industrial Structure - Wei, Zhixin; Liang, Shuai (International Journal of Social Sciences and Public Administration, 2024)
The change of RMB exchange rate is an important factor affecting Chinese economic operation, which has a far-reaching impact on the upgrading of Chinese industrial structure. This paper uses the data from 2014 to 2021 for empirical analysis, and concludes that the rise of RMB exchange rate has a promoting effect on the upgrading of Chinese industrial structure. Suggestions were put forward to accelerate the transformation and upgrading of traditional industries, develop emerging industries and high-tech industries, and encourage enterprises to increase investment in technological innovation and research and development.